Agrarian Conflict Intensifies Human Rights Violations and Ecosystem Damage: Konflik Agraria Memperparah Pelanggaran HAM dan Kerusakan Ekosistem - Pramono, Abelia Kanaya; Sitanggang, Blessyn Tio (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Agrarian conflict constitutes a structural dispute over land control, ownership, and utilization that is closely linked to access to essential life resources and environmental sustainability. Specific Background: In the case of marine sand sedimentation, competing interests between economic exploitation and community environmental rights generate tensions that directly affect coastal livelihoods and ecological balance. Knowledge Gap: Previous studies tend to examine agrarian conflict, environmental degradation, or human rights issues separately, leaving limited integrative analysis that connects legal, environmental, and human rights dimensions. Aims: This study aims to analyze agrarian conflict and its association with human rights violations and environmental degradation through a qualitative descriptive case-based approach. Results: Findings indicate that sedimentation activities reduce fishery yields, damage marine ecosystems, decrease employment opportunities, and lower community income, while weak governance, limited transparency, and minimal public participation intensify social vulnerability and conflict escalation. Novelty: The study offers an integrative analytical framework that positions agrarian conflict as a multidimensional phenomenon encompassing legal structures, environmental sustainability, and human rights obligations. Implications: Strengthening transparent governance, participatory decision-making, and environmental law enforcement is essential to ensure sustainable resource management and safeguard community rights. Highlights• Demonstrates linkage between resource exploitation and social vulnerability escalation• Identifies governance deficiencies as drivers of multidimensional disputes• Reveals ecosystem degradation alongside declining coastal livelihoods KeywordsAgrarian Conflict; Human Rights; Environmental Governance; Marine Sand Mining; Social Vulnerability